A multicenter study of 1-year mortality and walking capacity after spinal fusion surgery for cervical fracture in elderly patients - Takeshi Sasagawa; Noriaki Yokogawa; Hiroyuki Hayashi; Hiroyuki Tsuchiya; Kei Ando; Hiroaki Nakashima; Naoki Segi; Kota Watanabe; Satoshi Nori; Kazuki Takeda; Takeo Furuya; Atsushi Yunde; et al. (BMC Musculoskeletal Disorders, 2022)
Abstract Background The 1-year mortality and functional prognoses of patients who received surgery for cervical trauma in the elderly remains unclear. The aim of this study is to investigate the rates of, and factors associated with mortality and the deterioration in walking capacity occurring 1 year after spinal fusion surgery for cervical fractures in patients 65 years of age or older. Methods Three hundred thirteen patients aged 65 years or more with a traumatic cervical fracture who received spinal fusion surgery were enrolled. The patients were divided into a survival group and a mortality group, or a maintained walking capacity group and a deteriorated walking capacity group. We compared patients’ backgrounds, trauma, and surgical parameters between the two groups. To identify factors associated with mortality or a deteriorated walking capacity 1 year postoperatively, a multivariate logistic regression analysis was conducted. Results One year postoperatively, the rate of mortality was 8%. A higher Charlson comorbidity index (CCI) score, a more severe the American Spinal Cord Injury Association impairment scale (AIS), and longer surgical time were identified as independent factors associated with an increase in 1-year mortality. The rate of deterioration in walking capacity between pre-trauma and 1 year postoperatively was 33%. A more severe AIS, lower albumin (Alb) and hemoglobin (Hb) values, and a larger number of fused segments were identified as independent factors associated with the increased risk of deteriorated walking capacity 1 year postoperatively. Conclusions The 1-year rate of mortality after spinal fusion surgery for cervical fracture in patients 65 years of age or older was 8%, and its associated factors were a higher CCI score, a more severe AIS, and a longer surgical time. The rate of deterioration in walking capacity was 33%, and its associated factors were a more severe AIS, lower Alb, lower Hb values, and a larger number of fused segments.